(untitled) (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program aimed to enhance students’ environmental literacy, observational skills, and digital literacy through the implementation of project-based learning by developing a participatory digital herbarium at Sanggar Bimbingan Wira Damai, Batu Caves, Selangor, Malaysia. The program was initiated in response to challenges in biology learning, which tended to be theoretical, lacked documentation of local biodiversity, and showed limited student engagement in environmental exploration. The implementation involved 20 students and applied a combination of socialization, training, field exploration, and mentoring activities. Data were collected using pretest and posttest assessments, observation sheets, and documentation. The results indicated a significant improvement in learning outcomes, reflected by an increase in the mean score from 57.95 to 82.25, with an N-Gain of 0.58 (moderate category). In addition, the program successfully produced a web-based digital herbarium and demonstrated improvements in students’ observational skills, technological competence, and conservation awareness. Overall, the integration of project-based learning with biodiversity-based digital technology proved to be an effective and adaptive approach for improving biology learning quality in nonformal education settings with limited resources, while also providing sustainable learning tools for the partner institution.